The Functional Change and Deletion of FLC Homologs Contribute to the Evolution of Rapid Flowering in Boechera stricta - Lee, Cheng-Ruei; Hsieh, Jo-Wei; Schranz, M. E.; Mitchell-Olds, Thomas (Frontiers in Plant Science, 2018)
Differences in the timing of vegetative-to-reproductive phase transition have evolved independently and repeatedly in different plant species. Due to their specific biological functions and positions in pathways, some genes are important targets of repeated evolution – independent mutations on these genes caused the evolution of similar phenotypes in distantly related organisms. While many studies have investigated these genes, it remains unclear how gene duplications influence repeated phenotypic evolution. Here we characterized the genetic architecture underlying a novel rapid-flowering phenotype in Boechera stricta and investigated the candidate genes BsFLC1 and BsFLC2. The expression patterns of BsFLC1 suggested its function in flowering time suppression, and the deletion of BsFLC1 is associated with rapid flowering and loss of vernalization requirement. In contrast, BsFLC2 did not appear to be associated with flowering and had accumulated multiple amino acid substitutions in the relatively short evolutionary timeframe after gene duplication. These non-synonymous substitutions greatly changed the physicochemical properties of the original amino acids, concentrated non-randomly near a protein-interacting domain, and had greater substitution rate than synonymous changes. Here we suggested that, after recent gene duplication of the FLC gene, the evolution of rapid phenology was made possible by the change of BsFLC2 expression pattern or protein sequences and the deletion of BsFLC1.